2005
DOI: 10.1080/08035250410033943
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery intima‐media thickness and angiotensin‐converting enzyme gene polymorphism in the offspring of parents with premature stroke

Abstract: We conclude that determination of the carotid IMT and of the ACE I/D polymorphism do not permit discrimination of the cardiovascular risk in children of parents with or without premature stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Several studies have investigated genetic polymorphisms in candidate pathways implicated in the pathogenesis of atherosclerosis [43][44][45][46][47][48][49][50][51][52][53]. For instance, functional variants in the genes APO A-E [44,45,50], eNOS [47], PCK1 [48], PON1 [49], OPG [53], PPARG [52], and GPx-1 [51] are associated with carotid IMT or its risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated genetic polymorphisms in candidate pathways implicated in the pathogenesis of atherosclerosis [43][44][45][46][47][48][49][50][51][52][53]. For instance, functional variants in the genes APO A-E [44,45,50], eNOS [47], PCK1 [48], PON1 [49], OPG [53], PPARG [52], and GPx-1 [51] are associated with carotid IMT or its risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Such interaction was also described in children [13]. Other recent work concluded that determination of the ACE insertion/deletion polymorphism and carotid IMT did not help to discriminate the cardiovascular risk in the children of parents with or without premature stroke [14].…”
Section: Angiotensin-converting Enzyme and Coronary Artery Diseasementioning
confidence: 94%
“…ACE gene polymorphisms have been widely studied in stroke, after the report of increased risk of myocardial infarction in DD genotype carriers [Cambien et al, 1992]. We found three meta-analysis and 12 case-control studies (Table 4) [Casas et al, 2004;Banerjee et al, 2007;Ariyaratnam et al, 2007;Szolnoki et al, 2003;Karagiannis et al, 2004;Zhang et al, 2004;Varda et al, 2005;Brenner et al, 2005;Szolnoki et al, 2005;Dikmen et al, 2006aPera et al, 2006;Gormley et al, 2007;Lalouschek et al, 2007, Berger et al, 2007 on this subject. The meta-analysis of Casas et al [2004] reported an increased risk of stroke in D/D carriers.…”
Section: Platelet Receptorsmentioning
confidence: 99%